Synthesis and characterization of boron azadipyrromethene single-wall carbon nanotube electron donor-acceptor conjugates - Flavin, Kevin; Lawrence, Katherine; Bartelmeß, Jürgen; Tasior, Mariusz; Navio, Cristina; Bittencourt, Carla; O'Shea, Donal F.; Guldi, Dirk Michael; Giordani, Silvia (Acs Nano, 2011)
The preparation of a novel donor-acceptor material, consisting of a red/near-infrared (NIR) absorbing boron azadipyrromethene donor covalently attached to a highly functionalized single-wall carbon nanotube (SWNT) acceptor, which bears great potential in the field of organic photovoltaics, has been demonstrated. Both purification and covalent functionalization of SWNTs have been demonstrated using a number of complementary characterization techniques, including atomic force microscopy, Raman, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared, and NIR-photoluminescence spectroscopy, and a functionalization density of approximately 1 donor molecule per 100 SWNT atoms has been estimated by XPS. The redox behavior of the fluorophore has been investigated by electrochemistry and spectroelectrochemistry as well as by pulse radiolysis. The donor-acceptor properties of the material have been characterized by means of various spectroscopic techniques, such as UV-vis NIR absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy, and time-resolved transient absorption spectroscopy. Charge transfer from the photoexcited donor to the SWNT acceptor has been confirmed with a radical ion pair state lifetime of about 1.2 ns. © 2011 American Chemical Society.